An asparagine/glycine switch governs product specificity of human N-terminal methyltransferase NTMT2. (December 2018) - Dong, Cheng; Dong, Guangping; Li, Li; Zhu, Licheng; Tempel, Wolfram; Liu, Yanli; Huang, Rong; Min, Jinrong
Abstract α-N-terminal methylation of proteins is an important post-translational modification that is catalyzed by two different N-terminal methyltransferases, namely NTMT1 and NTMT2. Previous studies have suggested that NTMT1 is a tri-methyltransferase, whereas NTMT2 is a mono-methyltransferase. Here, we report the first crystal structures, to our knowledge, of NTMT2 in binary complex with S-adenosyl-L -methionine as well as in ternary complex with S-adenosyl-L -homocysteine and a substrate peptide. Our structural observations combined with biochemical studies reveal that NTMT2 is also able to di-/tri-methylate the GPKRIA peptide and di-methylate the PPKRIA peptide, otherwise it is predominantly a mono-methyltransferase. The residue N89 of NTMT2 serves as a gatekeeper residue that regulates the binding of unmethylated versus monomethylated substrate peptide. Structural comparison of NTMT1 and NTMT2 prompts us to design a N89G mutant of NTMT2 that can profoundly alter its catalytic activities and product specificities. Cheng Dong et al. resolve the crystal structure of NTMT2, presenting the molecular basis for substrate recognition. Using structural and biochemical studies, they identified a specific residue within NTMT2 that controls its binding affinity to unmethylated or monomethylated substrates.